Reforming world agricultural trade : a policy statement by twenty-nine professionals from seventeen countries (Institute for International Economics Washington D.C.US, 1988)
Describes the crisis in world agriculture focusing on weakening prices, rising protectionism and subsidies. Argues the case for urgent policy reform among GATT member states and outlines a 7 point framework which gives direction for continuing national changes in policy and the parameters for negotiating the final multinational trade agreement. Makes recommendations for reform of agricultural and trade policies in the context of the Uruguay Round. These relate to areas including farm programs, the environment, negotiation of GATT rules, participation by developing countries and dispute settlement. Reviews progress to date in agricultural reform in the European Community, the US and Japan.
IDS